2008
DOI: 10.1021/bi800869y
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Import of HSV-1 DNA Polymerase Processivity Factor UL42 Is Mediated by a C-Terminally Located Bipartite Nuclear Localization Signal

Abstract: The polymerase accessory protein of the human herpes simplex virus type 1 (HSV-1) DNA polymerase UL42 plays an essential role in viral replication, conferring processivity to the catalytic subunit UL30. We show here that UL42 is imported to the nucleus of living cells in a Ran- and energy-dependent fashion, through a process that requires a C-terminally located bipartite nuclear localization signal (UL42-NLSbip; PTTKRGRSGGEDARADALKKPK(413)). Moreover cytoplasmic mutant derivatives of UL42 lacking UL42-NLSbip a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 54 publications
0
41
0
Order By: Relevance
“…Processivity factors other than p41 of HHV-6 have been shown to contain a functional NLS (12,35,(37)(38)(39). Indeed, we observed that BMRF1 protein, when it was expressed alone, localized to the nucleus (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Processivity factors other than p41 of HHV-6 have been shown to contain a functional NLS (12,35,(37)(38)(39). Indeed, we observed that BMRF1 protein, when it was expressed alone, localized to the nucleus (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Sometimes nuclei were stained by incubating with DAPI (1 µg/mL) for 4 min at RT. Samples were washed with PBS, mounted on coverslips in PBS/glycerol 50% (v/v), and imaged using a Nikon Eclipse E600 microscope equipped with a Nikon DXM1200 digital camera and a Nikon Plan Fluor 40× objective (Nikon, Tokyo, Japan), essentially as previously [68]. Live cells grown on Willcodishes (Willcowells, Amsterdam, The Netherlands) were infected with TOZGFP-HSV1 [51] and analyzed for GFP expression using a Nikon Eclipse TE2000-U inverted microscope equipped with a Nikon DXM1200 digital camera and a Nikon Plan Fluor 40× objective (Nikon, Tokio, Japan), as previously [69][71].…”
Section: Methodsmentioning
confidence: 99%
“…Besides ssDNA binding protein, the two main complexes are a multimeric DNA polymerase holoenzyme and helicase/primase complexes. Given the high molecular weight of such proteins, their nuclear transport has been shown to be an active process mediated by a number of different IMPs, which recognize specific NLSs on the cargo proteins [52,53,54,55,56,57,58,59]. In some cases, individual subunits are capable of localizing to the cell nucleus independently of the others, like in the case of HSV and HCMV DNA polymerase holoenzyme subunits [52,53,54,55,56].…”
Section: Nuclear Transport Of Herpesviral Dna Replicating Enzymesmentioning
confidence: 99%
“…Given the high molecular weight of such proteins, their nuclear transport has been shown to be an active process mediated by a number of different IMPs, which recognize specific NLSs on the cargo proteins [52,53,54,55,56,57,58,59]. In some cases, individual subunits are capable of localizing to the cell nucleus independently of the others, like in the case of HSV and HCMV DNA polymerase holoenzyme subunits [52,53,54,55,56]. However in the case of KSHV and EBV DNA polymerase holoenzymes [59,60] and most of their helicase/primase complex subunits, formation of the holoenzyme appears to be a pre-requisite for nuclear transport [61,62,63,64] (see Table 1).…”
Section: Nuclear Transport Of Herpesviral Dna Replicating Enzymesmentioning
confidence: 99%
See 1 more Smart Citation